Hubungan Body Condition Score dengan Service Per Conception pada Induk Sapi Bali di Dusun Tempos Desa Tempos Kecamatan Gerung Lombok Barat : The Relationship Between Body Condition Score and Service Per Conception in Bali Cow in Tempos Subvillage Tempos Village Gerung District Lombok Barat - Ria Harmayani; Alimuddin Alimuddin; Fauzan Azima (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
The purpose of this study was to determine the relationship between Body Condition Score and Service Per Conception in Bali Cows in Tempos subvillage, Tempos Village, Gerung District, West Lombok Regency. The method used in this study is observational with a longitudinal study type. The sample used in this study was 30 Bali cattle. The observed variables are Body Condition Score (BCS) and Service Per Conception (SC). The results showed that the results of simple linear regression analysis obtained an F count of 28.615 with a significance of 0.000. the result of the correlation between Body Condition Score (BCS) and Service Per Conception (S/C) is -0.711 with a significant value of 0.000. R2 = -0.711. The coefficient of determination (KD) is 54.8%. It can be concluded that there is a relationship between Body Condition Score and Service Per Conception in Bali Cows in Tempos Hamlet, Tempos Village, Gerung District, West Lombok Regency with a contribution size of 54.8%.